Solidaritas Bank Sampah Berseri: Alternatif Program CSR Berbasis Pengelolaan Sampah Berkelanjutan Terintegrasi - Adinda Aulia Nur Afifah; Tunjung Baskoro Adi (Jurnal Intervensi Sosial dan Pembangunan, 2022)
This article aims to describe PT Pertamina Patra Niaga IT Balongan's CSR empowerment program based on integrated sustainable waste management in the Langgen Block, Singaraja Village, Indramayu. The initial initiation came from a resident's anxiety about the slum and dirty surrounding environment as a trigger for tidal flooding and digestive diseases. Since 2019, this waste management has been carried out based on solidarity from the collective consciousness and self-subsistent of the surrounding community, assisted by the village government through village funds. Then starting in 2021, this activity and its managers will become foster partners of PT Pertamina Patra Niaga IT Balongan CSR in the Serial Waste Bank CSR program. This study uses a descriptive qualitative method with observations and interviews with residents and managers of the Berseri Waste Bank including literature studies. The results of this study indicate that the Berseri Waste Bank CSR Program is an alternative CSR program that represents an integrated sustainable waste management pattern that has a broad impact on the environment, social, economy and welfare with the concept of Integrated Sustainable Waste Management (ISWM).Keywords: CSR, Integrated Sustainable Waste, Management Waste Management, Solidarity, Waste Bank.